2022
DOI: 10.3390/polym14245466
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled TLR7/8 Agonist-Mannose Conjugate as An Effective Vaccine Adjuvant for SARS-CoV-2 RBD Trimer

Abstract: Small synthetic TLR7/8-agonists can be used as vaccine adjuvants to enhance cell and humoral-mediated immune responses to specific antigens. Despite their potency, after local injection they can be dispersed to undesired body parts causing high reactogenicity, limiting their clinical applications. Here we describe a vaccination strategy that employs the covalent conjugate of a mannose and TLR7/8 agonist as a vaccine adjuvant to take advantage of mannose binding C-type lectins on dendritic cells to enhance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition, a mannose-TLR7/8 agonist adjuvant could enhance vaccine-induced humoral and cellular immune responses. 30 Chitosan is a promising adjuvant for the COVID-19 vaccines. For instance, Tatlow et al developed an inhaled chitosan-coated DNA vaccine and demonstrated its potential as a preventive COVID-19 vaccine.…”
Section: Natural Polymer Biomaterials In Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a mannose-TLR7/8 agonist adjuvant could enhance vaccine-induced humoral and cellular immune responses. 30 Chitosan is a promising adjuvant for the COVID-19 vaccines. For instance, Tatlow et al developed an inhaled chitosan-coated DNA vaccine and demonstrated its potential as a preventive COVID-19 vaccine.…”
Section: Natural Polymer Biomaterials In Sars-cov-2mentioning
confidence: 99%
“…Chitosan can induce inflammasome and promote cellular and humoral immunity by binding to cell surface receptors such as Toll-like receptor-2 (TLR-2) and stimulating the DNA sensor cGAS-STING pathway to induce dendritic cell (DC) maturation and TH1 immune response in type I interferons. In addition, a mannose-TLR7/8 agonist adjuvant could enhance vaccine-induced humoral and cellular immune responses …”
Section: Biomaterials Help To Anti-sars-cov-2 Strategiesmentioning
confidence: 99%
See 1 more Smart Citation